2012
DOI: 10.4102/phcfm.v4i1.371
|View full text |Cite
|
Sign up to set email alerts
|

Bite-to-hospital time and morbidity in victims of viper bite in a rural hospital in Nigeria

Abstract: BackgroundMortality amongst in-hospital patients bitten by carpet viper in northern Nigeria has reduced, related to use of a monospecific ovine Fab snake antivenom. However, many victims survive with temporary or permanent morbidity.ObjectivesStudy objectives were to: (1) determine and score the morbidity caused by carpet viper bite; and (2) find the relationship between bite-to-hospital time and morbidity amongst victims of carpet viper bite.MethodA prospective study was conducted in a rural hospital in north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
(20 reference statements)
2
23
1
Order By: Relevance
“…large vipers) avoid such human-trafficked areas which pose great human-detection risks. As in the majority of West African studies, and as recorded from all sections of our study population, three snake species were by far the commonest snakebite culprits; Carpet Viper, Night Adder Causus maculatus and Black-necked Spitting Cobra [16, 23, 26, 35, 40, 43, 45, 46]. These three species were also the commonest found in our study area, as shown by extensive ecological censuses [59].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…large vipers) avoid such human-trafficked areas which pose great human-detection risks. As in the majority of West African studies, and as recorded from all sections of our study population, three snake species were by far the commonest snakebite culprits; Carpet Viper, Night Adder Causus maculatus and Black-necked Spitting Cobra [16, 23, 26, 35, 40, 43, 45, 46]. These three species were also the commonest found in our study area, as shown by extensive ecological censuses [59].…”
Section: Discussionsupporting
confidence: 65%
“…Long delays in antivenom treatment often lead to severe cases of morbidity (e.g. amputations) or death, even if such treatment is administered correctly [22, 42, 44, 45]. It is therefore important to ascertain the extent of both untreated and delayed treatments in order to address these clinical and epidemiological shortcomings in the management of snakebites in remote rural parts of Ghana and sub-Saharan Africa [2, 13, 15, 40, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are convinced that this intervention should be replicated and its efficacy evaluated in other parts of southern Asia and elsewhere (e.g., Africa), where available transports are limited and where morbidity and mortality from snake bites are associated with increased bite-to-hospital time. 28,29 Cost-effectiveness analysis of the intervention would also help policy makers. In addition, other types of medical emergencies may also benefit from a community-based approach involving motorcycle volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…In the same country, patients admitted with symptoms of neurotoxicity and vomiting [ 22 , 24 ], coagulopathy and leukocytosis [ 23 ], hypertension, albuminuria, changes in bleeding and prothrombin time [ 25 ] were more likely to develop severe outcomes. The delay in antivenom administration was also a risk factor for severity in Nigeria [ 27 ]. Capillary leak syndrome, bleeding and respiratory paralysis were risk factors for mortality in patients who received snake antivenom in Nigeria and Korea [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%